Whole Genome Sequencing and Metabolomic Study of Cave Streptomyces Isolates ICC1 and ICC4 - Gosse, Jessica Thandara; Ghosh, Soumya; Sproule, Amanda; Overy, David; Cheeptham, Naowarat; Boddy, Christopher N. (Frontiers in Microbiology, 2019)
The terrestrial subsurface microbiome has gained considerable amount of interests in the recent years because of its rich potential resource for biomining novel genes coding for metabolites possessing antimicrobial activities. In our previous study, we identified two Streptomyces isolates, designated as ICC1 and ICC4, from the Iron Curtain Cave, Chilliwack, Canada that exhibited antagonistic activities against the multidrug resistant strains of Escherichia coli. In this study, the genomes of these two isolates were sequenced by Illumina MiSeq, assembled and annotated. The genes associated with secondary metabolite production were identified and annotated using the bioinformatics platforms antiSMASH and BAGEL. ICC1 and ICC4 were then cultivated and ICC1 metabolome characterized by UHPLC-ESI-HRMS. The Global Natural Products Social Molecular Networking was used to identify metabolites based on the MS/MS spectral data. ICC1 and ICC4 showed a high level of sequence identity with the terrestrial bacteria Streptomyces lavendulae; however, they possess a greater secondary metabolite potential as estimated by the total number of identified biosynthetic gene clusters (BGCs). In particular, ICC1 and ICC4 had a greater number of polyketide and non-ribosomal peptide BGCs. The most frequently detected BGCs were those predicted to generate terpenes, small and low complexity dipeptides and lipids. Spectral analysis clearly identified a number of diketopiperazine products through matched reference spectra for cyclo (Leu-Pro), cyclo (Pro-Val) and cyclo [(4-hydroxyPro)-Leu]. One of the terpenes gene clusters predicted by antiSMASH possesses a seven-gene pathway consistent with diazepinomicin biosynthesis. This molecule contains a very rare core structure and its BGC, to date, has only been identified from a single bacterial genome. The tetrapeptide siderophore coelichelin BGC was unambiguously identified in the genome, however, the metabolite could not be identified from the culture extracts. Two type III polyketides, 2′, 5′ – dimethoxyflavone and nordentatin, were identified from the UHPLC-HRMS data of the aqueous and n-butanolic fractions of Streptomyces sp. ICC1, respectively. A BGC likely encoding these metabolites was predicted in both genomes. The predicted similarities in molecule production and genome shared by these two strains could be an indicative of a cooperative mode of living in extreme habitats instead of a competitive one. This secondary metabolite potential may contribute to the fitness of ICC1 and ICC4 in the Iron Curtain Cave.